Investigating the Genetic Change in BRAF Gene Causing Manifestation of Prostate Cancer in a Sample of Iraqi Patients - Jaleel I. Asaad (Journal of Global Pharma Technology, 2020)
This study included 100 patients suffering prostate cancer, 15 persons with family history of cancer served as positive control, and 30 healthy men served as negative control.  Prostate cancer tissues were collected from surgical room and subjected to DNA extraction for further processing.  Four primers were designed to investigate lethal changes at BRAF location related to this disease. Six pathogenic mutations were found among patients included in this study. These were rs1131692058, rs180177042, rs397507484, rs121913364, rs121913377, rs113488022, and rs1131692058. These represented ingle nucleotide polymorphism except for rs1131692058 which was found a deletion mutation. More data showed that positive control were less specific to associate with BRAF primer suggesting they bear variations susceptible for lethal change that may developed to cancer.